Immunomodulatory, insulinotropic, and cytotoxic activities of phylloseptins and plasticin‐TR from the Trinidanian leaf frog Phyllomedusa trinitatis. (7th February 2019) - Pantic, Jelena; Guilhaudis, Laure; Musale, Vishal; Attoub, Samir; Lukic, Miodrag L.; Mechkarska, Milena; Conlon, J. Michael
Abstract : The aim of the study was to determine the in vitro immunomodulatory, cytotoxic, and insulin‐releasing activities of seven phylloseptin‐TR peptides and plasticin‐TR, first isolated from the frog Phyllomedusa trinitatis . The most cationic peptides, phylloseptin‐1.1TR and phylloseptin‐3.1TR, showed greatest cytotoxic potency against A549, MDA‐MB231, and HT‐29 human tumor‐derived cells and against mouse erythrocytes. Phylloseptin‐4TR was the most hydrophobic and the most effective peptide at inhibiting production of the proinflammatory cytokines TNF‐α and IL‐1β by mouse peritoneal cells but was without effect on production of the antiinflammatory cytokine IL‐10. Phylloseptin‐2.1TR and phylloseptin‐3.3TR were the most effective at stimulating the production of IL‐10. The noncytotoxic peptide, plasticin‐TR, inhibited production of TNF‐α and IL‐1β but was without effect on IL‐10 production. The results of CD spectroscopy suggest that the different properties of plasticin‐TR compared with the immunostimulatory activities of the previously characterized plasticin‐L1 from Leptodactylus laticeps may arise from greater ability of plasticin‐TR to oligomerize and adopt a stable helical conformation in a membrane‐mimetic environment. All peptides stimulated release of insulin from BRIN‐BD11 rat clonal β cells with phylloseptin‐3.2TR being the most potent and effective and phylloseptin‐2.1TR the least effective suggesting that insulinotropic potency correlates inversely with helicity. The study has provided insight into structure‐activity relationships among the phylloseptins. The combination of immunomodulatory and insulinotropic activities together with low cytotoxicity suggests that phylloseptin‐3.3TR and plasticin‐TR may represent templates for the development of agents for use in antiinflammatory and type 2 diabetes therapies. Abstract : Phylloseptins and plasticin‐TR from the frog Phyllomedusa trinitatis to varying degrees inhibit production of proinflammatory cytokines TNF‐α and IL‐1β, stimulate production of antiinflammatory IL‐10, are cytotoxic to human tumor‐derived cells, and stimulate insulin secretion by BRIN‐BD11 clonal β cells.